A CASE REPORT: THE STAGED RETRO AURICULAR FLAPS FOR AURICLE RECONSTRUCTION AFTER TRAUMATIC AMPUTATIONS - Suparman, Alexandria Stephanie; Doni Setiawan; Yugos Juli Fitra (Universitas Airlangga, 2023)
Highlights: Instances of severe ear injuries are uncommon. The paragraph explores the efficacy of the staged retro-auricular flap (SRF) as a proficient approach to ear reconstruction. SRF demonstrates the ability to successfully reinstate the ear's dimensions, contour, and functionality, yielding highly satisfactory functional and aesthetic outcomes. Abstract: Introduction: A complete amputation or other severe auricular injury is rare. The amputated ear also presents a significant problem for the plastic surgeon. Case Illustration: A 29-year-old man had his left ear amputated due to trauma presented. He cut off his ear to get rid of the whisper because he has a history of psychiatric illnesses and complaints about hearing them. The remaining portion of the cartilage that was still linked to the ear attachment area was sutured to the preserved cartilage. The defect is covered using a stage pedicle flap. A skin transplant was used to close the donor flap's retro-auricular defect, which was its secondary defect. Discussion: A random-pattern flap with an abundant vascular supply is the staged retro-auricular flap (SRF). This flap's main disadvantage is the two-stage process required to complete it. Excellent cosmetic outcomes can be achieved by matching skin color and texture well in the postauricular sulcus, mastoid area, and posterior ear. Conclusion: SRF is an efficient ear reconstruction technique that offers relatively little operational morbidity and can restore the ear's size and shape with good to exceptional functional and cosmetic results when used on appropriately chosen helical ear abnormalities.